Assessment Patterns in Islamic Education Learning on Fiqh Material: Pola Penilaian dalam Pembelajaran Pendidikan Agama Islam pada Materi Fiqih - Batubara, Alwi Umar; Matsum, Hasan (Halaqa: Islamic Education Journal, 2025)
This study aims to analyze the implementation pattern of assessment of Islamic religious education learning in fiqh material at SMAS Budi Agung Medan. The focus of the discussion is on the pattern of implementation of assessment, the effectiveness of the pattern of implementation of assessment, and what are the supporting factors and inhibiting factors as well as solutions to the pattern of implementation of assessment at SMAS Budi Agung Medan. The research method used is qualitative with a phenomenological approach. The data collection techniques used are observation, interview, and documentation. The overall data obtained was then analyzed using the miles and huberman technique, namely data reduction, data display, and conclusion drawing. The results showed that the pattern of assessment implementation at SMAS Budi Agung Medan is carried out with three types, first diagnostic assessment, second formative assessment, third summative assessment. These three types are very effectively implemented and have long-term feedback and benefits. The supporting factors are school facilities, and the inhibiting factors are schools, teachers, parents and students at SMAS Budi Agung Medan. Highlights: Three Assessment Types: The school implements diagnostic, formative, and summative assessments effectively. Effective Implementation: These assessments provide long-term feedback and benefits in the learning process. Supporting and Inhibiting Factors: Facilities support success, while issues from schools, teachers, parents, and students pose challenges. Keywords: Pattern, Assessment, Jurisprudence